Tolak Ukur Pembebasan Pajak Bagi Lembaga Perkreditan Desa (LPD) Di Wilayah Provinsi Bali - I Wayan Bandem; I Nyoman Suandika (Universitas Mahendradatta, 2019)
As Article 1 paragraph (3) of the State Constitution of the Republic of Indonesia is the stateof Indonesia is a state of law. Understanding the rule of law is simply a country whose administrationof power is based on law. and Article 1 paragraph (1) of the 1945 Constitution that the Indonesian stateis a Republican unitary state with a government structure that is the Government, Provincial RegionalGovernment, Regency / City Regional Government and the lowest government is the VillageGovernment which has their respective leaders based on legislation applicable legislation. Inconnection with the establishment of the LPD in article 33 of the 1945 Constitution and in Article 18Bparagraph (2) of the 1945 Constitution of the Republic of Indonesia which reads